Architecture and Structure – Just a Simple Love Affair - Manfred Grohmann (Civil Engineering Dimension, 2015)
Behind challenging architecture there is always a challenging structure. To achieve the optimal result in a design process, architecture and structure have to be developed together. Starting from the first planning phases, the cooperation has to be a fruitful dialog involving complex geometry programs and structural calculation tools. The result of such planning processes is exemplified in this paper presenting just 2 projects Bollinger+Grohmann realized together with two different architects, i.e. The Rolex Learning Center for Ecole Polytechnique Federate de Lausanne (EPFL) in Lausanne with SANAA, Tokyo, and the new building for the European Central Bank (ECB) in Frankfurt with COOP Himme (1) blau Vienna. The aim is to prove that there is no contradiction between new architecture and structure, but just a simple love affair.